Comparison studies on solid state diffusion of Ni–Ti and Ni–TiH2 under CaH2 reducing environment - Mohd Zaki, Hafizah Hanim; Abdullah, Jamaluddin (Elsevier, 2014)
Phase formation of NiTi via solid state diffusion from Ni–Ti and Ni–TiH2 powders under a CaH2 reducing environment were investigated. Elemental powder sintering of Ni–Ti at equiatomic composition did not result in single phase TiNi, but rather in multi-phases, including Ti2Ni, TiNi, and TiNi3. In this work, we show evidence that powder sintering of Ni–TiH2 produces single phase NiTi with good transformation heat both on cooling and heating with ΔHA–M=26.04 J/g and ΔHM–A=25.53 J/g, respectively. The use of CaH2 as the in situ reducing agent and of TiH2 to replace Ti as the starting powder, protected the sample successfully from oxidation.